2009
DOI: 10.1128/jcm.00601-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRSA Select Agar, CHROMagar Methicillin-Resistant Staphylococcus aureus (MRSA) Medium, and Xpert MRSA PCR for Detection of MRSA in Nares: Diagnostic Accuracy for Surveillance Samples with Various Bacterial Densities

Abstract: Rapid laboratory methods provide optimal support for active surveillance efforts to screen for methicillinresistant Staphylococcus aureus (MRSA). Most laboratories struggle to determine the optimal use of resources, considering options to balance cost, speed, and diagnostic accuracy. To assess the performance of common methods, the first comparison of MRSASelect agar (MS) and CHROMagar MRSA (CA), with and without broth enrichment followed by a 24-h subculture to MS, was performed. Results were compared to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 26 publications
1
37
1
1
Order By: Relevance
“…Broth enrichment is frequently mentioned as an adjunct to plated medium and molecular methods to enhance the detection of MRSA in patient specimens. Many publications have reported increases in the recovery of MRSA and calculated statistical performance achieved at the expense of marginally increased recoveries of MRSA, increased work load, increased effort, longer time to detection and the impediment to expedient enforcement of hospital infection control practices (17,20,24,25,34), in addition to the associated increased costs. Broth enrichment methods need to be standardized as to optimal growth medium, incubation time and temperature, the influence of sampling schedules, single versus multiple body sites, and the correlation of MRSA bioburden levels from body sites other than nares, and the correlation of such MRSA bio-burden loads in broth enrichment only to the actual transmission rates of MRSA to others.…”
Section: Discussionmentioning
confidence: 99%
“…Broth enrichment is frequently mentioned as an adjunct to plated medium and molecular methods to enhance the detection of MRSA in patient specimens. Many publications have reported increases in the recovery of MRSA and calculated statistical performance achieved at the expense of marginally increased recoveries of MRSA, increased work load, increased effort, longer time to detection and the impediment to expedient enforcement of hospital infection control practices (17,20,24,25,34), in addition to the associated increased costs. Broth enrichment methods need to be standardized as to optimal growth medium, incubation time and temperature, the influence of sampling schedules, single versus multiple body sites, and the correlation of MRSA bioburden levels from body sites other than nares, and the correlation of such MRSA bio-burden loads in broth enrichment only to the actual transmission rates of MRSA to others.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Wolk et al demonstrated that a lower MRSA colonization burden is associated with discordant screening tests (positive PCR test and negative agar test), and the MRSA cycle threshold (C T ) values for the concordant samples in the Xpert MRSA assay (Cepheid, Sunnyvale, CA) were statistically lower than those for discordant samples (21). In our study, we examined the variation between PCR and direct culture screening methods for nasal MRSA colonization among hospitalized veterans, compared the C T values for patients with discordant screening results at admission and discharge, and evaluated the quantitative abilities of the Xpert MRSA PCR assay.…”
mentioning
confidence: 99%
“…Several recent studies have compared the BDGO and Xpert MRSA assays in countries with a high prevalence of MRSA (22,29,(34)(35)(36). In our study, we not only compared classical performance parameters like sensitivity, specificity, PPV, and NPV in an area with a low prevalence but also analyzed the likelihood of discrepant PCR and culture results for specimens from body sites other than the nares.…”
Section: Discussionmentioning
confidence: 99%